2022
DOI: 10.3390/fishes7060360
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Moringa oleifera Leaves Nanoparticles on Growth Performance, Physiological, Immunological Responses, and Liver Antioxidant Biomarkers in Nile tilapia (Oreochromis niloticus) against Zinc Oxide Nanoparticles Toxicity

Abstract: The current study addresses the influence of Moringa oleifera leaves nanoparticles (MO-NPs) on growth, biochemical, immunological, and hepatic antioxidant alterations induced by zinc oxide nanoparticles toxicity in Nile tilapia (O. niloticus). Fish (N = 180) were divided into four groups with replicates. The first one was set as a control group and the second group was fed an MO-NPs-enriched diet (2.5 g/kg diet). The third group was exposed to 8 mg/L ZnO-NPs, while the forth group was exposed to 8 mg/L ZnO-NPs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…The experimental diets revealed that ALT, AST, T-bilirubin, D-bilirubin, and BUN values were significantly not different compared to the control diet, indicating that the experimental diets did not have a detrimental effect on liver and kidney function. Similarly, Nile tilapia fed Moringa oleifera leaf nanoparticle-supplemented diets did not increase the ALT and AST values [66].…”
Section: Discussionmentioning
confidence: 85%
“…The experimental diets revealed that ALT, AST, T-bilirubin, D-bilirubin, and BUN values were significantly not different compared to the control diet, indicating that the experimental diets did not have a detrimental effect on liver and kidney function. Similarly, Nile tilapia fed Moringa oleifera leaf nanoparticle-supplemented diets did not increase the ALT and AST values [66].…”
Section: Discussionmentioning
confidence: 85%
“…It is necessary to study the potential effects and useful applications of nanotechnology in solving problems in aquaculture. Studies like this can be used in aquaculture and environmental safety by identifying the potential risks and informing guidelines for the safe use of nanoparticles in aquatic environments, developing new treatments for fish diseases, improving water quality, and environmental remediation (Hamed et al, 2022). Our previous study focused on the effects of Fe-NPS on the liver, growth, and immune system of stellate sturgeon (Ebrahimi et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Plant extracts achieved a success in the aquaculture industry as dietary supplements in promoting growth and immunity. Dietary supplementation of Moringa oleifera leaf nanoparticles (MO-NPs) can act as a growth promoter and immune-antioxidant stimulator [4]. Moreover, hydroxytyrosol (HT), a kind of polyphenol with a small molecular weight, is the most efficient antioxidant in olives and is considered a mitochondrial nutrient.…”
Section: Fish Nutrition and Physiologymentioning
confidence: 99%